2013
DOI: 10.1159/000348448
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Regulation Skills Training Enhances the Efficacy of Inpatient Cognitive Behavioral Therapy for Major Depressive Disorder: A Randomized Controlled Trial

Abstract: Background: Deficits in emotion regulation skills are possible factors maintaining major depressive disorder (MDD). Therefore, the aim of the study was to test whether integrating a systematic emotion regulation training (ERT) enhances the efficacy of routine inpatient cognitive behavioral therapy (CBT) for MDD. Methods: In a prospective randomized controlled trial, 432 inpatients meeting criteria for MDD were assigned to receive either routine CBT or CBT enriched with an intense emotion regulation skills trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
171
1
18

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 262 publications
(207 citation statements)
references
References 74 publications
(106 reference statements)
10
171
1
18
Order By: Relevance
“…Numerous studies indicate that deficits in emotion regulation may be a relevant factor for the development and persistence of mental health symptoms (32,33). Emotion regulation skills have been shown to be promising for reducing a broad range of such symptoms (34). While …”
Section: Study Conditionmentioning
confidence: 99%
“…Numerous studies indicate that deficits in emotion regulation may be a relevant factor for the development and persistence of mental health symptoms (32,33). Emotion regulation skills have been shown to be promising for reducing a broad range of such symptoms (34). While …”
Section: Study Conditionmentioning
confidence: 99%
“…At work, people often must cope with difficult situations and solve problems while also addressing the challenging emotions that arise in those situations. Because deficits in the ability to adaptively cope with difficult emotions are related to various mental health problems (64), the use of effective emotion-regulation techniques (65) in low-threshold internet-based stressmanagement training appears promising (66,67).…”
Section: Study Limitationsmentioning
confidence: 99%
“…We also showed in another systematic review that dismantling and other component studies in depression are even more severely underpowered (Cuijpers, Cristea, Karyotaki, Reijnders, & Hollon, 2010). Of the 19 identified component studies of psychotherapies for depression, only one had sufficient power to detect a relevant differential effect between the treatment with the added component (emotional regulation) and the standard therapy without the component (Berking, Ebert, Cuijpers, & Hofmann, 2013). Incidentally, this study also found a significant benefit of the added component over the standard therapy.…”
mentioning
confidence: 67%